An implementation algorithm of a carrier-based PWM technique for three-phase four-leg voltage sag generator with microcontroller - Worrajak Muangjai (2018)
This paper presents an implementation of a carrier-based PWM (CBPWM) technique for three-phase four-leg voltage sag source generator with microcontroller. Recently, the implementation of the 3D SVPWM for three-phase four-leg voltage source it seems to be the easiest way to generated voltage sag and it might be a software and hardware burden even for recent digital signal processor (DSP) systems but needs quite a bit of digital logic and computational power. Therefore, this paper presents a simple sag algorithm CBPWM technique for three-phase four-leg voltage sag source generator its very simple design, low-cost and can be easily develop and operate hardware structure. The proposed technique can be implemented with microcontroller and testing algorithm compare with 3D SVPWM technique. The performance of proposed CBPWM strategy has been investigated and verified through simulations and experimental results for three-phase four-leg voltage source generator. © 2013 IEEE.